Detection Beyond Debye's Length with an Electrolyte‐Gated Organic Field‐Effect Transistor. (6th November 2014) - Palazzo, Gerardo; De Tullio, Donato; Magliulo, Maria; Mallardi, Antonia; Intranuovo, Francesca; Mulla, Mohammad Yusuf; Favia, Pietro; Vikholm‐Lundin, Inger; Torsi, Luisa
<x xml:space="preserve">Abstract</x> Electrolyte‐gated organic field‐effect transistors are successfully used as biosensors to detect binding events occurring at distances from the transistor electronic channel that are much larger than the Debye length in highly concentrated solutions. The sensing mechanism is mainly capacitive and is due to the formation of Donnan's equilibria within the protein layer, leading to an extra capacitance (CDON) in series to the gating system. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>